2020
DOI: 10.1186/s12883-020-01989-6
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the LDL subclasses in ischemic stroke as a risk factor in a Chinese population

Abstract: Background Acute ischemic stroke (AIS) is one of the leading causes of mortality and long-term disability worldwide. Our study aims to clarify the role of low-density lipoproteins (LDL) subclasses in the occurrence of AIS and develop a risk xprediction model based on these characteristics to identify high-risk people. Methods Five hundred and sixty-six patients with AIS and 197 non-AIS controls were included in this study. Serum lipids and other baseline characteristics including fasting blood glucose (GLU), … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…LDL3 and LDL4 are subtypes with higher concentrations of sdLDL-C. in our research, we also found a signi cant positive correlation between LDL3 and LDL4 levels and the severity of coronary artery stenosis. Our study illustrated that the sdLDL-C level was positively correlated with traditional cardiovascular risk factors, including TC, TG, and LDL-C, which is consistent with the results of a previous study [33]. To identify people at high cardiovascular risk, we constructed a model that included the evaluation of clinical variables in cardiovascular risk factors.…”
Section: Discussionsupporting
confidence: 88%
“…LDL3 and LDL4 are subtypes with higher concentrations of sdLDL-C. in our research, we also found a signi cant positive correlation between LDL3 and LDL4 levels and the severity of coronary artery stenosis. Our study illustrated that the sdLDL-C level was positively correlated with traditional cardiovascular risk factors, including TC, TG, and LDL-C, which is consistent with the results of a previous study [33]. To identify people at high cardiovascular risk, we constructed a model that included the evaluation of clinical variables in cardiovascular risk factors.…”
Section: Discussionsupporting
confidence: 88%
“…Foam cells could fuse and burst, releasing large amounts of cholesterol that form the core of atherosclerotic plaque. This process could also aggravate AS and affect the outcomes of stroke (30)(31)(32). Dobiasova et al found that the AIP value was inversely proportional to the diameter of oxidized LDL particles and indirectly showed sdLDL particle size, which could be used as an indirect method to reflect LDL particle size instead (33).…”
Section: Discussionmentioning
confidence: 99%
“…In stark contrast, sdLDL has been considered to have more atherogenic effect than other LDL particles due to its increased susceptibility to oxidation, high endothelial permeability, and decreased hepatic LDL receptor affinity [ 36 , 37 ]. Previous studies demonstrate that sdLDL-C is a new risk factor for cardiovascular events [ 11 , 15 , 16 , 38 ]. For instance, one previous study suggested that sdLDL-C concentrations were a better marker for assessment of coronary heart disease (CHD) than total LDL-C [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since evidence showed that patients who took lipid-lowering drugs and reached the set LDL-C level were still at risk of cardiovascular and cerebrovascular events [ 13 , 14 ]. Previous studies related to the sdLDL-C mainly focused on the patients who have experienced cardiovascular and cerebrovascular events [ 15 , 16 ]. For instance, studies have shown that sdLDL-C is an independent risk factor for IMT in acute ischemic stroke [ 17 ], as well as for unstable plaques in acute cerebral infarction (ACI) patients [ 18 ].…”
Section: Introductionmentioning
confidence: 99%